2013
DOI: 10.3174/ajnr.a3560
|View full text |Cite
|
Sign up to set email alerts
|

Neuroradiologic Features in X-linked α-Thalassemia/Mental Retardation Syndrome

Abstract: BACKGROUND AND PURPOSE: X-linked ␣-thalassemia/mental retardation syndrome (Mendelian Inheritance in Man, 301040) is one of the X-linked intellectual disability syndromes caused by mutations of the ATRX gene and characterized by male predominance, central hypotonic facies, severe cognitive dysfunction, hemoglobin H disease (␣-thalassemia), genital and skeletal abnormalities, and autistic and peculiar behavior. More than 200 patients in the world, including Ͼ70 Japanese patients, have been diagnosed with ATR-X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 11 publications
(9 reference statements)
1
24
0
Order By: Relevance
“…Our index cases showed remarkable widespread white matter 209 changes on brain MRI. These findings supported the previous sugges-210 tion that ATRX is involved in normal myelination, or the mutated pro-211 tein affects the expression of other proteins during myelination 212 (Wada et al, 2013). Therefore, we emphasize the importance of brain Korea to date (Yun et al, 2011).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Our index cases showed remarkable widespread white matter 209 changes on brain MRI. These findings supported the previous sugges-210 tion that ATRX is involved in normal myelination, or the mutated pro-211 tein affects the expression of other proteins during myelination 212 (Wada et al, 2013). Therefore, we emphasize the importance of brain Korea to date (Yun et al, 2011).…”
supporting
confidence: 83%
“…Since the typical case was first de-49 scribed in 1990 (Wilkie et al, 1990), a broad spectrum of atypical clini-50 cal manifestations was noted (Pavone et al, 2010;Basehore et al, 2014). 51 Moreover, Wada et al recently reported various neuroimaging findings 52 of ATRX syndrome, which included white matter abnormalities, as well 53 as nonspecific brain atrophy (Wada et al, 2013). 54 In this study, we present two cases of genetically confirmed ATRX 55 syndrome that were identified by whole-exome sequencing ( …”
mentioning
confidence: 87%
See 1 more Smart Citation
“…General information: X‐linked intellectual disability syndrome due to ATRX mutations on Xq13.3. More than 200 patients reported by 2012 …”
Section: Glossarymentioning
confidence: 99%
“…However, these studies have focused on acquired anemia, whereas few studies have focused on hereditary anemia. Previous studies with small sample sizes have demonstrated a trend of developing cognitive dysfunction in severe types of thalassemia and the hemoglobin mutations associated with β thalassemia minor [11][12][13]. However, studies elucidating the relationship between thalassemia and long-term dementia incidence are rare.…”
Section: Introductionmentioning
confidence: 99%